Workshop “Strategi Digital Marketing dan Sosial Media Sebagai Media Promosi Produk dan Meningkatkan Kompetensi Siswa Untuk Berwirausaha di SMK N 4 Kota Jambi - Silvia Rianti Agustini; hendri; Eni Rohaini; Inggrit Tia Pratiwi (LPPM Universitas Dinamika Bangsa, 2023)
SMK N 4 Jambi City has 4 vocational programs, namely Catering/Culinary, Fashion, Hospitality and Beauty. The program aims to make students have skills that are able to compete in the world of work and collaborate with agencies in the industrial revolution era. Therefore, the purpose of this activity is to provide practical knowledge in the field of management science in digital marketing strategy and social media as a media for product promotion and increase student competence for entrepreneurship. The methods used are direct material, questions and answers and discussions about marketing management, regulations on the use of social media such as the ITE Law, consumer protection laws, trade law, and digital marketing training, the weaknesses and strengths of digital marketing, and regulations related to this activity. and identification of targeted consumers/markets, making it possible to maximize marketing activities with digital marketing strategies so that they can assist in promoting and increasing student/I competence in entrepreneurship which is also the goal of SMK N 4 Jambi City, namely to be able to form students capable of entrepreneurship nationally and internationally